Improvement of the Physical and Oxidative Stability Characteristics of Ice Cream through Interesterified Moringa oleifera Oil: Moringa oleifera Oil for Ice Cream Improvement - Nadeem, Muhammad; Ullah, Rahman; Ullah, Ansar (Biological Sciences - PJSIR, 2016)
This study aimed to investigate the effect of high melting point interesterified M. oleifera oil (35.6oC) with substantial amount of unsaturated fatty acids on physicochemical and oxidative stability characteristics of ice cream. Of the 10% fat in the ice cream, 30% was replaced by interesterified M. oleifera oil at three levels i.e. 10, 20 and 30% (T1, T2 and T3, respectively). Oleic acid increased from 26.55% to 31.69%, 36.94% and 42.15% in T1, T2 and T3 with no effect on melting time, compositional attributes and free fatty acid content of ice cream (P>0.05). Supplementation of ice cream with interesterified M. oleifera oil inhibited the autoxidation process in ice cream during 3 months storage period (P<0.05).The loss of oleic and linoleic acid in fresh and 3 months stored control and T2 was 26.55%, 24.15%, 26.39% and 1.93%, 1.24% and 1.79%, respectively. Peroxide value of three months stored control and T3 was 1.12 and 0.39 (meqO2/kg). The overall acceptability score of T2 was 80% of the total score (9).